Doctor´s formation in Cuba. A critical perspective of its history. - Carmen Niurka Piña Loyola; Marta Rosa González Debén; Ana Margarita López Rodríguez; Magdalena López Rodríguez del Rey (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
In this work a historic análisis is made about the teaching of Medicine in Cuba, since its beguining back in 1726 until present days, that is why the study has three stages: Colony, Neocolony, and Revolution, with the aim of carrying out a hystorical reflection on the formation of the physician in Cuba. We use history as a methodological criterium, but it is interesting to highlight the evolution of practical and political ideas that mark the tendencies and regularities of the process in question.